CURRENT TRENDS OF ECONOMIC DIPLOMACY OF UKRAINE IN THE MIDDLE EAST - ZASTAVNYI, Andrii; IVASHCHUK, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The role of economic diplomacy in establishing and developing relations between countries has been substantiated, explained by the priority of economic interests. The aim of the article is to analyze the current trends of Ukraine’s economic diplomacy in the Middle East. The historical prerequisites for the formation of Ukraine’s economic diplomacy and the main vectors of its foreign economic policy have been revealed. The dynamics of the regional structure of goods export from Ukraine have been analyzed, confirming that the countries of the CIS were in the focus of Ukraine’s economic diplomacy in the initial stages of independence. Changes in Ukraine’s foreign economic policy after 2014 have been established, and the importance of cooperation with Middle Eastern countries has been argued. Emphasis is placed on cooperation with Turkey, the main trade partner for Ukraine among the Middle Eastern countries. An assessment of the dynamics of the foreign trade activity of both countries has been conducted, and the main vectors of cooperation, which include economic and investment spheres, cultural and educational cooperation, have been substantiated. The peculiarities of Ukraine’s cooperation with Turkey since the beginning of the war have been highlighted. Using the SWOT analysis methodology, the strengths and weaknesses, opportunities, and threats in Ukraine’s cooperation with the Middle East countries have been identified. The main consequences of expanding Ukraine’s partnership with Middle Eastern countries, which will contribute to the diversification of trade between countries, the development of joint infrastructure projects, etc., have been singled out. Strategic directions for expanding Ukraine’s presence in the Middle East countries have been proposed. Among the channels of disseminating information about Ukraine, attention is focused on the work of Ukraine’s diplomatic missions abroad. It is proposed to revise the format of presenting information about Ukraine in the Middle East countries, involving representatives of foreign media. The effectiveness of using social media platforms and business channels for Ukraine’s strategic penetration into the markets of this region has been confirmed. Other channels for forming Ukraine’s image diplomacy in the Middle East have been identified. Prospective vectors of Ukraine’s economic diplomacy in the region have been outlined.